Assessing the network power capacity of Informal International Governmental Organizations (IIGO): comparing BRICS and MIKTA - PARLAR DAL, EMEL (My University, 2022)
This paper examines the conditions under which informal groupings such as BRICS and MIKTA create and sustain networks that are able to effectively influence global governance architecture, and compares the level of that network power from a state-centric perspective and covering the period until February 2022. In doing so, it uses a network power capacity (hereafter NPC) framework derived from Hafner-Burton et al. (Int Organ 63(3):559-592, 2009) work on Networks Analysis in International Relations, which is based on five main variables: (1) the existence of strong states within informal groupings, (2) the existence of strong intra-economic and institutional ties, (3) common norms, values, and culture among members of IIGOs, (4) the level of power symmetry among the members of the informal grouping and (5) the engagement of IIGO members in the networks of existing, established powers through the signature of agreements. In the final analysis, it concludes that BRICS has a stronger NPC than MIKTA, since it has (1) a higher number of powerful members, (2) stronger intra-institutional and economic ties, (3) greater congruence of shared norms and values by its members and (4) more members engaged with the existing established powers (namely the USA and the EU) through the signing of bilateral and multilateral agreements.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Bilim, Teknoloji ve Toplum; Siyaset Bilimi; Uluslararası İlişkiler; Social Sciences and Humanities; Sociology; Science, Technology and Society; Political Science; International Relations; ULUSLARARASI İLİŞKİLER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SİYASET BİLİMİ; INTERNATIONAL RELATIONS; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); POLITICAL SCIENCE; Siyasi bilimler ve Uluslararası İlişkiler; Genel Sosyal Bilimler; Sosyal Bilimler ve Beşeri Bilimler; Political Science and International Relations; General Social Sciences; Social Sciences & Humanities; Rising powers; BRICS; MIKTA; Network power; Informality; Global governance; RATIONAL DESIGN; GOVERNANCE; POLICY; COOPERATION; LAW; ANARCHY; CRISIS